High strength and ductility in a new Mg–Zn–Ga biocompatible alloy by drawing and rotary forging - Stanislav O. Rogachev; Viacheslav E. Bazhenov; Alexander A. Komissarov; Denis V. Ten; Anna V. Li; Vladimir A. Andreev; Eugene S. Statnik; Iuliia A. Sadykova; Sofia V. Plegunova; Viacheslav V. Yushchuk; Nikolay A. Redko; Alexey I. Salimon; et al. (Results in Materials, 2024)
A comparative study of the effect of drawing and rotary forging on the structure, mechanical and corrosion properties of a new biodegradable magnesium alloy Mg–2Zn–2Ga was carried out. The original 6 mm diameter bars obtained by hot extrusion were reduced to the diameters in the range 5.5–3.3 mm by drawing or rotary forging. Optical microscopy, scanning electron microscopy and EBSD grain orientation mapping were used to characterize the material microstructure. Tensile testing was performed to determine the mechanical properties. The optimum temperature for rotary forging and annealing after each drawing pass for defect-free bar production was found to be 300 °C. The combination of the highest strength and ductility was achieved in the 4.2 mm diameter drawn bar and is explained by the formation of numerous twin boundaries in the alloy structure. The 3.3 mm diameter bar obtained by drawing as well as the 5.5 mm diameter bar obtained by rotary forging showed a balance between high strength (260–310 MPa) and large elongation (9–12 %). The analysis of the stress-strain curves using Hollomon's equation was conducted. The hydrogen evolution test in Hanks' solution revealed that the drawn bars of diameters 4.2 and 5.2 mm, as well as the rotary forged bar of 5.5 mm possessed 3 times lower corrosion resistance reduced in comparison with the original 6 mm extruded bar. The 3.3 mm diameter drawn bar exhibited the lowest nominal corrosion rate of 0.11 mm/year that offers excellent opportunities for use in medical implants.